Correlation between dental caries experience and mutans streptococci counts by microbial and molecular (polymerase chain reaction) assay using saliva as microbial risk indicator - S G Damle; Ashish Loomba; Abhishek Dhindsa; Ashu Loomba; Vikas Beniwal (Wolters Kluwer Medknow Publications, 2016)
Background: The aim of this study was to assess the relationships of quantitative salivary levels of mutans streptococci (MS) in children, aged 3-6 years and 12-15 years, exhibiting variable patterns of caries activity, and to compare the association of MS in saliva using microbial and molecular (polymerase chain reaction [PCR]) assay. Materials and Methods: In this cross-sectional observational study, eighty children were included, forty children each in Group I (3-6 years) and Group II (12-15 years). Children were further divided into two subgroups (Group IC, INC and Group IIC, IINC) based on their dental caries status. Saliva samples were collected and plated onto Mitis Salivarius-Bacitracin agar plates. After detection of MS, DNA was isolated and purified, and MS were evaluated using the PCR and AP-PCR. Results: Of the selected 80 children, 42 were male and 38 were female. In Group IC, the mean colony count was 2.27 ± 0.54 × 105 CFU/ml, and in Group INC, the mean colony was found to be 1.61 ± 0.54 × 105 CFU/ml. In Group II, where mean colony count of 3.31 ± 0.85 × 105 CFU/ml and 2.44 ± 0.54 × 105 CFU/ml was observed in Group IIC and Group IINC, respectively. Conclusion: The mean colony count increased with increasing age and was also more in children with dental caries. Based on the matrices generated by the PCR analysis using coefficient slipped-strand mispairing, wide range of genetic diversity was seen in cases of children with and without clinically detectable caries.